Iron deficiency and its impact to children’s cognitive and development - Rini Sekartini (Indonesian Nutrition Association, 2023)
Children are born to learn, and they develop and learn very quickly in their early years. Brain development milestones in children aged 0-5 years and Iron plays an important role in many neurodevelopmental processes, and animal studies have shown that adequate iron requirements in pregnancy and childhood are critical for a child's brain and neurodevelopment.